ChemInform Abstract: Ruthenium‐Catalyzed Reductive Coupling of 1, 3‐Enynes and Aldehydes by Transfer Hydrogenation: anti‐Diastereoselective Carbonyl Propargylation. Issue 20 (25th April 2013) - Geary, Laina M.; Leung, Joyce C.; Krische, Michael J.
Abstract Good levels of anti‐diastereoselectivity in propargylation of aliphatic aldehydes and enals are displayed by the presented ruthenium‐based catalyst system whereas the corresponding additions to aryl aldehydes remain unselective.